Stability of orange (Citrus sinensis) and mandarin (C. reticulata) pulp nectar mix with xanthan gum and cmc - Macías Andrade, Edison Fabian (2022)
The objective of the present investigation was to evaluate the stability of a nectar mix of orange pulp (Citrus sinensis) and mandarin (C. reticulata) with xanthan gum and CMC. The factors in studies were two: A: types of stabilizers (xanthan gum and CMC) and B: percentage of orange and mandarin pulp (50/50, 60/40 and 70/30). The experimental design applied was a DCA with a bifactorial arrangement A*B (2 x 3), resulting in six treatments with three replications for each one of them, 240 mL of nectar mix, consisting of pulp, water, sugar and stabilizer, were used for each experimental unit. The physical-chemical variables were evaluated (acidity, pH, density and stability), for the data analysis the statistical program SPSS version 22 was used. In conclusion, the nectar mix of orange and mandarin showed that the pH variables whose value is lower at 4.5 as indicated by the INEN 2337: 2008 Standard, density (1.064 to 1.069 g·mL-1) and 0% sedimentation presented the best physical-chemical characteristics in T1, T2 and T3 using xanthan gum.